HUBUNGAN PENDIDIKAN ORANG TUA DENGAN MOTIVASI BELAJAR PKn SISWA - Wati Susiawati (Universitas Muhammadiyah Prof Dr Hamka, 2016)
This research aims to know how is parent's education includes educational level and motivation to learn civics students in SD Islam Al-Khairiyah Cilegon. Sampling was conducted using random sampling (a random number). The sample of research was 25 students (10% of the population). The conclusion is the education level of the parents in SD Islam Al-Khairiyah Cilegon belonging to the education level is still low. It can be seen from the calculation of the questionnaire that was answered by the students that most of the recent education graduates majority of their parents SD / MI alone. Civics students' learning motivation level in SD Islam Al-Khairiyah Cilegon have very high motivation terutapa on citizenship education lessons.